2018
DOI: 10.3389/fmicb.2018.01029
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Finger Millet Indigenous Rhizobacterium Pseudomonas sp. MSSRFD41 in Blast Disease Management—Growth Promotion and Compatibility With the Resident Rhizomicrobiome

Abstract: Finger millet [Eleusine coracona (L). Gaertner] “Ragi” is a nutri-cereal with potential health benefits, and is utilized solely for human consumption in semi-arid regions of Asia and Africa. It is highly vulnerable to blast disease caused by Pyricularia grisea, resulting in 50–100% yield loss. Chemical fungicides are used for the management of blast disease, but with great safety concern. Alternatively, bioinoculants are widely used in promoting seedling efficiency, plant biomass, and disease control. Little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 84 publications
0
21
0
1
Order By: Relevance
“…In our case the improved finger millet and pigeon pea growth may be primarily due to the choice of AMFpp and AMFfm which were originally isolated from the rhizosphere of pigeon pea and finger millet respectively via screening (Rao et al, 1983a,b;Reddy and Bagyaraj, 1991). Similarly the PGPR strain MSSRFD41 was isolated from finger millet and may have been co-evolved as better symbiont for the host (Sekar et al, 2010(Sekar et al, , 2018. The observed variation in the microbial performance across the sites and years could be attributed to the differences in the soil physio-chemical properties and climate (Supplementary Table 1).…”
Section: Biofertilizer Effect On Grain Yieldmentioning
confidence: 82%
“…In our case the improved finger millet and pigeon pea growth may be primarily due to the choice of AMFpp and AMFfm which were originally isolated from the rhizosphere of pigeon pea and finger millet respectively via screening (Rao et al, 1983a,b;Reddy and Bagyaraj, 1991). Similarly the PGPR strain MSSRFD41 was isolated from finger millet and may have been co-evolved as better symbiont for the host (Sekar et al, 2010(Sekar et al, , 2018. The observed variation in the microbial performance across the sites and years could be attributed to the differences in the soil physio-chemical properties and climate (Supplementary Table 1).…”
Section: Biofertilizer Effect On Grain Yieldmentioning
confidence: 82%
“…Interspecies interactions may affect the abundance of some soil microbial populations, but they do not affect population diversity ( Li et al, 2018 ; Yu et al, 2019 ). Previous research has shown that the above-mentioned dominant bacterial groups participate in soil N and P cycling ( Fierer et al, 2012 ; Zhang et al, 2016 ; Pham et al, 2018 ; Sekar et al, 2018 ), which improves the growth of medicinal plants. Actinomycetes found for ecological sites in the soil or the plant rhizosphere environment directly prevents pathogens from infecting plants, and reduces the number of pathogens through spatial competition and antibiosis ( Samac et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA gene was amplified from the representative isolates of the BOX-PCR cluster groups using universal primers 27F (5′-AGA GTT TGA TCM TGG CTC AG-3′) and 1492R (5′-TAC GGH TAC CTT GTT ACG ACT T-3′) ( Sekar et al, 2018 ). Each 20 μl reaction containing 6 μl of 2X ampliqon red mix, 2 μl of 2.5 pmol 27F and 1492R primers, 2 μl of 50 ng template DNA was made up to 20 μl using double sterilized HPLC water.…”
Section: Methodsmentioning
confidence: 99%